Striving for self-improvement: alternative medicine considered as technologies of enhancement. Issue 3 (August 2018) - Pedersen, Inge
Abstract The notion of medical enhancement technologies has drawn attention to optimization techniques within the health area. However, this notion has evolved at the level of governmental programmes, with very little attention directed towards people's own practices. Using a social scientific body of knowledge about enhancement technologies and a Foucauldian analytical framework, this article explores how users engage with alternative medicine. Drawing on in-depth interviews with Danish users and observations of their treatment sessions, the article demonstrates how they embark on a voyage of discovery with the body to enhance their own selves and bodily resources. The discussion centres on Rose's approach to medical enhancement technologies and Foucault's notion of 'technologies of the self'. A wider field of tension is outlined in which embodied alternative treatment practices play a role in various modalities of transforming and controlling bodies and selves. It is argued that such practices can be conceived of as enhancement technologies at the users' level by showing how they not only concentrate on treatment and body maintenance, but also foster the enabling processes of changing habits, preferences, and attitudes, and creating a subjective sense of their bodies.